Fear of me: experiences of health residents in the Covid-19 pandemic - Oyama, Ricardo Massuda [UNESP]; Luna, Willian Fernandes; Cyrino, Eliana Goldfarb [UNESP] (Univ Estadual Paulista-unesp, 2024)
The Covid-19 pandemic has affected health professionals, including residents. This study aims to reflect on the impacts of the pandemic on the mental health of residents in the context of medical and multiprofessional residency and the implications for the training process of these professionals. It is a qualitative research study involving interviews conducted with medical and multiprofessional residents, utilizing thematic content analysis. Health residents were at the forefront of confronting the pandemic and are considered vulnerable professionals due to their exposure to the virus and psychological distress, such as fear of illness. They experienced the effects of social distancing, both as a measure to prevent transmission and due to concerns from family members and cohabitants, resulting in feelings loneliness. The study reveals impacts on mental health, highlighting the importance of planning actions to provide and enhance the training of health residents.
Keywords: Internship and residency; Covid-19; Mental health; Fear; Professional training